2017
DOI: 10.1007/s00436-017-5534-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of preservative and mounting media on the size and shape of monogenean sclerites

Abstract: Based on Cichlidogyrus sp. (Monogenea, Ancyrocephalidae) specimens from Hemichromis sp. hosts, we tested the influence of different methods to fix/preserve samples/specimens [frozen material, alcohol or formalin preserved, museum process for fish preservation (fixed in formalin and preserved in alcohol)] and different media used to mount the slides [tap water, glycerin ammonium picrate (GAP), Hoyer's one (HM)] on the size/shape of sclerotized parts of monogenean specimens. The results show that the use of HM s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…5 ). The observed size differences may be due to two factors: 1) the mounting medium used when making the slides: Fankoua et al [7] demonstrated that the use of Hoyer’s increases the size and modifies the shape of sclerotized parts, and/or 2) the way Paperna & Thurston [35] made the drawings and took the measurements for the original description. Although measurements given in the original description are compatible with its drawings and scale bars ( Table 2 ), there are significant differences between these measurements and those we took from the type slide ( Table 2 ) (an exception is the ventral bar total length, which seems incomparable: we measured the length of a branch while the original authors probably measured the total length of the bar).…”
Section: Resultsmentioning
confidence: 99%
“…5 ). The observed size differences may be due to two factors: 1) the mounting medium used when making the slides: Fankoua et al [7] demonstrated that the use of Hoyer’s increases the size and modifies the shape of sclerotized parts, and/or 2) the way Paperna & Thurston [35] made the drawings and took the measurements for the original description. Although measurements given in the original description are compatible with its drawings and scale bars ( Table 2 ), there are significant differences between these measurements and those we took from the type slide ( Table 2 ) (an exception is the ventral bar total length, which seems incomparable: we measured the length of a branch while the original authors probably measured the total length of the bar).…”
Section: Resultsmentioning
confidence: 99%
“…Morphometric parameters where subsequently analysed by principal component analysis (PCA) in the R software package stats [35] and visualised using ggplot2 [36]. Only specimens mounted on slides with GAP were part of the analyses to avoid effects of the staining method on the results [37]. The following variables were used in PCA: (1) the ratios body width/total length (TL), (2) body length/TL, (3) pharynx length/TL, (4) pharynx width/TL, (5) diameter of the pseudohaptor/TL, (6) number of sclerite rows/TL, (7) testes maximum width/TL, (8) germarium length/TL and (9) germarium width/TL.…”
Section: Parasite Collection and Morphological Examinationmentioning
confidence: 99%
“…Jika napas sulit, berikan oksigen. Dapatkan bantuan medis (96,(193)(194)(195)(196)(197)(198)(199)(200)(201)(202)(203)(204)(205)(206)(207)(208)(209)(210)(211) . Catatan dokter : Ssetelah paparan inhalasi, amati selama 24 s.d 72 jam sebagai edema paru mungkin tertunda…”
Section: Bahayaunclassified